PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAAN DAN LOYALITAS KONSUMEN DI RUMAH SAKIT UMUM DAERAH KABUPATEN PASURUAN - Intan Perwita Sari (STIE Mandala Jember, 2016)
To increase customer loyalty in an organization, aspects of service quality and job satisfaction is very important to be used as a benchmark for improvement and organizational development. Basically because consumers have different needs and desires, so it needs to be served in a different way as well. The aim in this study was to verify and analyze the effect of service quality on customer satisfaction and customer loyalty. The population in this research are patients who are in hospitals and hospitals Bangil Pasuruan. Sampling method using purposive sampling technique, so that with this technique obtained a sample of 100 respondents in the two locations of the study. The population in this research are patients who are in hospitals and hospitals Bangil Pasuruan. Sampling method using purposive sampling technique, so that with this technique obtained a sample of 100 respondents in the two locations of the study. Measurements on technical research instruments using a Likert scale. Methods of data analysis using Path Analysis with SPSS 20. Based on the results of path analysis showed that: the first track shows that, quality service have positive and significant effect on customer satisfaction. While on the second line, indicating that the quality of service has a positive and significant impact on customer loyalty. in addition, customer satisfaction is also positive and significant impact on customer loyalty.